Analysis the Impact of Corruption on Investment in Iraq - علي ازهار حسن (Journal of Economics and Administrative Sciences, 2017)
There are different types of corruptions such as administrative, political, economic and financial corruption. The corruption forms also varied such as bribery, nepotism and extortion. All types and forms of corruption play significant role in the all economic variables generally and on investments in particular, and the corruption used to be an intermediate means in reducing the rate of economic growth. The corruption contributes in reducing the domestic investments via pay bribery by investors to officials’ persons for supplemental contracts and tenders which finally leads to reduction in the investment efficiency. The corruption also contributes in rise of operational costs for the investment projects. In addition, it contributes in providing inappropriate environment to inflow the foreign investments into hosted countries particularly those with high level of corruption. Iraq is among the countries with high level of corruption according to the corruption perceptions index via the low range of this index. Moreover, Iraq has been listed in the bottom according to the Transparency International Organization which lists the countries from the lower corruption to the highest. The corruption play negative role in investment reduction through reducing the ratio of domestic investment to GDP as well as reducing the foreign direct investment to Iraqi economy. The paper finds through ARDL estimation that there is a long run nexus between the corruption and the ratio of domestic investment to GDP. In addition, the econometric estimation discovered that there is long run and short run relationship between the corruptions and the ratio of foreign investment to GDP in Iraq during the period (2003-2016) by using quarterly data.